Genetic stock identification reveals greater use of an oceanic feeding ground around the Faroe Islands by multi-sea winter Atlantic salmon, with variation in use across reporting groups. (18th October 2022) - O'Sullivan, Ronan James; Ozerov, Mikhail; Bolstad, Geir H; Gilbey, John; Jacobsen, Jan Arge; Erkinaro, Jaakko; Rikardsen, Audun H; Hindar, Kjetil; Aykanat, Tutku
Abstract: While it is known that the oceans around the Faroe Islands support an Atlantic salmon ( Salmo salar ) feeding ground, the relative use of this resource by different age classes and populations remains largely unexplored. Using genetic stock identification and run–reconstruction modelling, we observed a consistent pattern whereby the proportion of multi-sea winter salmon (MSW—fish that have spent multiple winters at sea) for a reporting group was substantially greater around the Faroes than the MSW proportion among that group's corresponding pre-fisheries abundance. Surprisingly, MSW fish from Ireland and the United Kingdom were as likely to occur around the Faroes as were MSW fish from more north-eastern regions. While 1SW salmon (single sea-winter fish) from Ireland and the United Kingdom as well as Southern Norway occurred in similar proportions around the Faroes, 1SW fish from the north-eastern regions were virtually absent. Our results indicate that the oceans around the Faroes host a predominantly MSW feeding ground and use of this resource varies across age classes and reporting groups. Furthermore, these results suggest that MSW fish from some reporting groups preferentially migrate to the Faroes. Variation in spatial resource use may help buffer salmon populations against localized negative changes in marine conditions via portfolio effects.